Optical performance monitoring advanced techniques for next-generation photonic networks - Chan, Calvin C. K. (Academic Press/Elsevier, 2010)
This in-depth, detailed reference presents for the first time a comprehensive treatment of recent advances in optical performance monitoring. Written by leading experts in the field, the book provides an overview of recent developments in the area and the role of OPM in future optical systems and networks. Detailed discussions of various advanced techniques are provided to illustrate their principles. FEATURES: Presents the principles and applications of advanced OPM techniques, together with a comparative evaluation of their effectiveness in monitoring individual parameters, such as optical signal-to-noise ratio, chromatic dispersion, and polarization mode dispersion Explains the principles of the various advanced optical signal processing techniques and their applications in OPM Examines the role and applications of OPM in optical networks, including optical transport networks, coherent optical systems, and long-haul optical transmission systems Discusses the current approaches of OPM in the global standard SDH/SONET This book is ideal for technical professionals and researchers who want to understand and evaluate advanced techniques in OPM and their impact on the practical design of next-generation optical systems and networks. Provides a thorough and detailed discussion of the latest optical performance monitoring (OPM) techniques and their applications, presenting a comparative analysis of each method Contains high-quality technical contributions from leading experts, covering both principles and practical aspects of advanced OPM techniques Addresses challenges and opportunities related to OPM in next-generation reconfigurable optical systems and networks.